The quality of entrepreneurial activity and economic competitiveness in European Union countries: A panel data approach - Valentina Diana Rusu; Adina Dornean (Administrative Sciences, 2019)
To increase competitiveness, a country has to outperform its competitors in terms of research and innovation, entrepreneurship, competition, and education. In this paper, we aim to test the relationship between the quality of entrepreneurial activity and the economic competitiveness for the European Union countries by using panel data estimation techniques. Our research considers a sample of 28 EU countries over the period 2011-2017. For the empirical investigation we apply panel data regression models. The results obtained show that business, macroeconomic environment and the quality of entrepreneurship are significant determinants of economic competitiveness of EU countries. Thus, we identify significant positive relations between innovation rate, inflation rate, FDI and economic competitiveness, and significant negative relations between expectations regarding job creation, tax rate, costs and competitiveness. Our study completes the literature by analyzing the relationship between the quality of entrepreneurship and the competitiveness of countries, for an extensive sample formed by all the 28 countries members of the European Union for a period of seven recent years.
Keywords: 350; entrepreneurship; global competitiveness index; innovation; job creation; panel data